CT-M8 Mice: A New Mouse Model Demonstrates That Basophils Have a Nonredundant Role in Lupus-Like Disease Development - Tchen, John; Simon, Quentin; Chapart, Léa; Pellefigues, Christophe; Karasuyama, Hajime; Miyake, Kensuke; Blank, Ulrich; Benhamou, Marc; Daugas, Eric; Charles, Nicolas (Frontiers in Immunology, 2022)
Tissue-specific mouse models are essential tools to decipher the role of each cell compartment and/or their expressed genes in the pathophysiology of diseases. Here, we describe a new knock-in mouse model allowing expressions of both the fluorescent protein tdTomato and the CRE recombinase selectively in the basophil compartment, under the control of the Mcpt8 gene. These “CT-M8” mice did not show any abnormalities in their peripheral distribution of major immune cell populations nor in their basophil function. CT-M8 mice allowed the identification of basophils by immunofluorescence and flow cytometry, and basophil-specific Cre-mediated floxed gene deletion. Breeding of our CT-M8 mice with the ROSA26flox-stop-DTA mice led to the generation of basophil-deficient mice with no detectable abnormalities in other cell compartments. These mice were then used to document basophil involvement in systemic lupus erythematosus (SLE) pathophysiology since we previously reported by transient depletion of these cells during the course of an ongoing disease that they support and amplify autoantibody production in two distinct lupus-like mouse models (Lyn–/– and pristane-induced). Here, constitutive basophil deficiency prevented pristane-induced lupus-like disease development by limiting autoantibody titers and renal damages. Therefore, basophils have a non-redundant role in pristane-induced lupus-like disease and are involved in both its induction and amplification. This CT-M8 new mouse model will allow to finely decipher the role of basophils and their expressed genes in health and disease.